The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ijms242015175
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Atherosclerosis Biomarkers by Proteomics: A Focus on Lesion Pathogenesis and Vulnerability

Gabriele Nieddu,
Marilena Formato,
Antonio Junior Lepedda

Abstract: Plaque rupture and thrombosis are the most important clinical complications in the pathogenesis of stroke, coronary arteries, and peripheral vascular diseases. The identification of early biomarkers of plaque presence and susceptibility to ulceration could be of primary importance in preventing such life-threatening events. With the improvement of proteomic tools, large-scale technologies have been proven valuable in attempting to unravel pathways of atherosclerotic degeneration and identifying new circulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 184 publications
0
3
0
Order By: Relevance
“…The study conducted by Loftus et al [50] about the expression of MMP-9 within this tissue demonstrated a significant increase in MMP-9 localized in the most unstable carotid plaques and the plaques of more symptomatic patients. Interestingly, MMP-9 has been considered an excellent candidate for future pharmacotherapy intended to stabilize carotid plaques and prevent stroke [86].…”
Section: Plaque Ulcerationmentioning
confidence: 99%
“…The study conducted by Loftus et al [50] about the expression of MMP-9 within this tissue demonstrated a significant increase in MMP-9 localized in the most unstable carotid plaques and the plaques of more symptomatic patients. Interestingly, MMP-9 has been considered an excellent candidate for future pharmacotherapy intended to stabilize carotid plaques and prevent stroke [86].…”
Section: Plaque Ulcerationmentioning
confidence: 99%
“…The study conducted by Loftus et al [51] on the expression of MMP-9 within this tissue demonstrated a significant increase in MMP-9 localized in the most unstable carotid plaques and the plaques of more symptomatic patients. Interestingly, MMP-9 has been considered an excellent candidate for future pharmacotherapy intended to stabilize carotid plaques and prevent stroke [89].…”
Section: Plaque Ulcerationmentioning
confidence: 99%
“…In addition, serum and plasma are readily available in most biobanks, thus saving time and effort in specimen collection and facilitating biomarker discovery. Consequently, the discovery of new diagnostic markers from serum and plasma is actively pursued worldwide [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%